2017
DOI: 10.1037/fam0000292
|View full text |Cite
|
Sign up to set email alerts
|

Mother, father, and adolescent self-control and adherence in adolescents with Type 1 diabetes.

Abstract: This study explored whether shared self-control across a family system, including adolescent, mother, and father self-control, as well as the interaction of mother and father self-control, was associated with ease of completing adherence tasks, and the completion of adherence behaviors related to the type 1 diabetes (T1D) regimen. 137 adolescents (M = 13.48 years), mothers, and fathers completed a self-report measure of self-control, while adolescents also self-reported on ease of completing adherence tasks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(83 reference statements)
3
10
0
Order By: Relevance
“…In diabetes, another chronic disease population of adolescents who must also use injectable therapies, self-control in both parents and children has been shown to be associated with higher medication adherence in the adolescents. 30 Future research should evaluate the reasons for decreases in quality of life with increasing parental involvement in youth with MS. Based on the aforementioned work, it may relate to adolescent perceptions of self-control. Interventions might focus on these functional and psychosocial aspects of cognition to improve patient self-management and independence in managing their MS treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes, another chronic disease population of adolescents who must also use injectable therapies, self-control in both parents and children has been shown to be associated with higher medication adherence in the adolescents. 30 Future research should evaluate the reasons for decreases in quality of life with increasing parental involvement in youth with MS. Based on the aforementioned work, it may relate to adolescent perceptions of self-control. Interventions might focus on these functional and psychosocial aspects of cognition to improve patient self-management and independence in managing their MS treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the family is important in adolescent adherence [8]. Family conflict and negative communication around diabetes management, especially blood glucose monitoring, are common barriers to adolescent adherence to the diabetes regimen [9].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of T1D interventions promoting adherence in youth concluded that behavioral interventions without a focus on the personal and interpersonal aspects of the disease were less likely to affect blood glucose control [10]. Therefore, interventions focusing on adolescent adherence and disease management should not ignore the importance of the family, particularly family communication around T1D management tasks, in this process [8].…”
Section: Introductionmentioning
confidence: 99%
“…self-regulation, the ability to modulate cognitions, emotions, and behaviors toward long-term goals, is a key individual difference that has been associated with adherence behaviors, including SMBG, and glycemic control (Lansing, Crochiere, Cueto, Wiebe, & Berg, 2017;McNally, Rohan, Pendley, Delamater, & Drotar, 2010;Perez et al, 2016). A multicomponent, web-delivered intervention designed to target biopsychosocial processes in the self-regulation of SMBG in adolescents with above-target glycemic control was developed and tested, showing improvements in SMBG and HbA1c at 6-and 12-month follow-ups (Stanger, Lansing, Scherer, Budney, Christiano, & Casella, 2018).…”
mentioning
confidence: 99%